Sequential Treatments of Rimsulfuron, Mesotrione, Thifensulfuron, Balance Flexx, Cinch, Cinch ATZ, and Prowl H2O Mixtures for Weed Control in Irrigated Corn - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2015)
No treatment with less than 1.5 lb/a atrazine provided commercially acceptable Palmer amaranth control. The best level of Palmer amaranth control was produced by treatments that had good preemergence control augmented by a postemergence application with two or more modes of action that contained 0.5 lb/a atrazine. All treatments provided excellent kochia control. The best Russian thistle treatments provided from 77 to 88% control. The best foxtail or crabgrass treatments provided from 91 to 94% control. Combinations of preemergence treatments followed by a postemergence treatment achieved excellent shattercane control.
Keywords: weed science; weed control; rimsulfuron; thifensulfuron; Balance Flexx (isoxaflutole); Cinch (S-metolachlor); Cinch ATZ (Cinch+atrazine); Prowl H20 (microencapsulated pendimethalin); broadleaf and grass weed control in irrigated corn; glyphosate-resistant corn; shattercane; green foxtail; crabgrass; kochia; Palmer amaranth; Russian thistle; preemergence herbicide; postemergence herbicide